(untitled) (World Economics and Finance Bulletin, 2025)
Positive psychology issues are among the topics receiving increasing attention in accounting literature. This is due to their impact on managers’ behavior when making decisions regarding the disclosure of forward-looking information. However, there is a scarcity of research in this field in developing countries, particularly in the Iraqi context. Therefore, this study investigate the potential influence of the psychological capital (PsyCap) of managers on both the level and tone of forward-looking disclosure (FLD). To achieve this objective, a descriptive analytical approach was adopted. Data were collected using a questionnaire, with a total of 220 questionnaires distributed to a sample of managers, investors, Auditors of auditing firms, and financial analysts in 2024, of which 214 responses were retrieved. The research hypotheses were tested based on the data collected from the questionnaire. This paper reached several conclusions. Companies disclose forward-looking information at varying levels and tones (positive, neutral, negative), as companies often manage this disclosure. There is a significant relationship between three elements of PsyCap (self-efficacy, hope, resilience) and the level of FLD, as well as a relationship between two elements of PsyCap (hope, optimism) and the tone of FLD. This paper recommends that regulators should establish guidelines regarding the level and tone of FLD.